Comparison of beta enolase and myoglobin as histological markers of rhabdomyosarcoma. Issue 11 (November 1985) - Royds, J A; Variend, S; Timperley, W R; Taylor, C B
Abstract : A comparative study of beta enolase and myoglobin as markers of muscle differentiation in rhabdomyosarcoma was carried out, using an immunoperoxidase peroxidase antiperoxidase technique. Material from 26 cases of childhood rhabdomyosarcoma was studied and subdivided into embryonal and alveolar types. Positive cytoplasmic staining for beta enolase was seen in 85% of tumours studied (91% alveolar, 79% embryonal), whereas positive staining for myoglobin was detected in only 69% of tumours (82% alveolar, 64% embryonal). beta Enolase and myoglobin are useful in the histological diagnosis of rhabdomyosarcoma, and of the two, beta enolase seems to be the more sensitive.